QUANTITATIVE ANALYSIS OF INCOME DISTRIBUTION AND POVERTY MEASURES - Akhmedova Mavluda, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article provides a comprehensive quantitative analysis of income distribution and poverty measures, focusing on the assessment of income inequality and the depth, severity, and incidence of poverty within an economy. Using officially reported household income and expenditure data, the research applies widely recognized statistical and econometric tools, including the Gini coefficient, Lorenz curve, Theil index, and Foster–Greer–Thorbecke (FGT) poverty measures. The study aims to identify structural disparities in income allocation, evaluate poverty dynamics across population groups, and examine the sensitivity of poverty indicators to changes in income distribution. Descriptive statistics and inequality decomposition techniques are employed to capture both inter-group and intra-group income differences, while trend analysis is used to evaluate temporal changes in poverty levels. The findings reveal persistent income inequality and highlight the uneven distributional effects of economic growth, with vulnerable households disproportionately exposed to poverty risks. The results emphasize the importance of evidence-based social and fiscal policies aimed at inclusive growth, targeted income support, and effective poverty reduction strategies. The study contributes to the empirical literature by offering a statistically robust framework for monitoring income inequality and poverty and provides practical insights for policymakers and researchers engaged in socio-economic development planning.